Designing a Model of the Impact of Talent Management on Human Capital with the Mediating Role of Organizational Innovation - Abutaleb , Farhad; Sadjadi Hezaveh , Seyyed Hamid; Zarei , Ali; Ashraf Ganjouei , Farideh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The study aimed to design a model of the impact of talent management on human capital with the mediating role of organizational innovation (a case study of the Tehran Municipality Sports Organization).Methodology: This research employed a descriptive-correlational method. The statistical population included all employees (managers and experts) of the Tehran Municipality Sports Organization, totaling 300 individuals. The sample size was equal to the population size, employing a census method. Data collection tools included the standard Talent Management Questionnaire by Phillips and Roper (2009), the Organizational Innovation Questionnaire by Omid et al. (2002), and the Human Capital Questionnaire by Ghorbani et al. (2013). For data analysis, SPSS and LISREL software were utilized.Findings: The results indicated a significant relationship between talent management and organizational innovation and between talent management and human capital. However, while there was a significant relationship between organizational innovation and human capital, the mediating role of organizational innovation in the relationship between talent management and human capital was not confirmed.Conclusion: The overall conclusion of the research is that human resources are considered the most valuable capital of any organization and are central to development. It is evident that the Tehran Municipality Sports Organization, in its path toward growth and development, requires precise planning for this capital and the utilization of talent management and organizational innovation.